2013
DOI: 10.1007/s11239-013-0875-2
|View full text |Cite
|
Sign up to set email alerts
|

The Swiss cohort of elderly patients with venous thromboembolism (SWITCO65+): rationale and methodology

Abstract: Venous thromboembolism (VTE) is common and has a high impact on morbidity, mortality, and costs of care. Although most of the patients with VTE are aged ≥65 years, there is little data about the medical outcomes in the elderly with VTE. The Swiss Cohort of Elderly Patients with VTE (SWITCO65+) is a prospective multicenter cohort study of in- and outpatients aged ≥65 years with acute VTE from all five Swiss university and four high-volume non-university hospitals. The goal is to examine which clinical and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 47 publications
1
123
0
Order By: Relevance
“…with a smaller number of VTE events (n=157) showed that only 35% of venous thrombosis in IBD patient’s occurred in hospitalized patients 21 . This outpatient predominance is not unique to IBD with other studies demonstrating that inpatients account for 18% to 30% of VTE occurring in the general population 2224 . However the fact that twice the VTE burden in the IBD population occurs in the inpatient setting (compared to non-IBD matched controls) suggests that a larger fraction of VTE may thus be ‘preventable’ in those with IBD.…”
Section: Discussionsupporting
confidence: 43%
“…with a smaller number of VTE events (n=157) showed that only 35% of venous thrombosis in IBD patient’s occurred in hospitalized patients 21 . This outpatient predominance is not unique to IBD with other studies demonstrating that inpatients account for 18% to 30% of VTE occurring in the general population 2224 . However the fact that twice the VTE burden in the IBD population occurs in the inpatient setting (compared to non-IBD matched controls) suggests that a larger fraction of VTE may thus be ‘preventable’ in those with IBD.…”
Section: Discussionsupporting
confidence: 43%
“…12 A detailed description of the study methods has been published previously. 12 Briefly, consenting consecutive patients aged $65 years with objectively diagnosed, symptomatic DVT or PE were prospectively identified and followed over time. The ethics committee at each participating center approved the study, which followed the Helsinki protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome was the recurrence of symptomatic, objectively confirmed VTE within 12 and 24 months of D-dimer testing, defined as symptomatic new DVT or PE, based on predefined imaging criteria or autopsy as previously described. 12 Three blinded, independent experts adjudicated all recurrences.…”
Section: Org Frommentioning
confidence: 99%
“…A full description of the cohort methods, including eligibility criteria, definition of VTE, and follow-up procedures, has been published elsewhere. 17,18 Anticoagulant treatment (i.e., parenteral anticoagulant followed by vitamin K antagonists or parenteral anticoagulation alone) was left to the discretion of the managing hospital and primary care physicians. For this project, we excluded all patients who did not receive oral anticoagulation with vitamin K antagonists within 14 days of the index VTE event.…”
Section: Cohort Samplementioning
confidence: 99%